2017
DOI: 10.12691/jfnr-5-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nonanal-wax as Postharvest Fungicide of Tomato against <i>Botrytis cinerea</i>

Abstract: The antifungal activity of nonanal against Botrytis cinerea, one of the most important postharvest diseases of tomato gray mold, was tested by in vitro and in vivo experiments. Results of in vivo tests demonstrated that wax + nonanal treatment significantly decreased the incidence of gray mold during the entire storage period. After 8 d of storage, the disease incidences in Wax + nonanal (1×, 4× or 10× MFC)-treated fruits were 46.7%, 56.7%, 73.3%, respectively, in contrast to 100% of the control fruits. Loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…e antimicrobial activities of 1,3-oxazine against Enterococcus faecalis and Listeria monocytogenes were also reported by Hamza et al [42]. e antimicrobial activity of nonanal was reported by Zhang et al [43]. e antimicrobial potential of hydrazinecarbothioamide against Bacillus subtilis, E. coli, Staphylococcus aureus, Pseudomonas aeruginosa, Paenibacillus macerans, and Salmonella typhimurium was reported by Shim et al [44].…”
Section: Well Diffusion Agar Antimicrobial Activity Of Tunichrome Was Reported By Sugumaran and Robinsonmentioning
confidence: 68%
See 1 more Smart Citation
“…e antimicrobial activities of 1,3-oxazine against Enterococcus faecalis and Listeria monocytogenes were also reported by Hamza et al [42]. e antimicrobial activity of nonanal was reported by Zhang et al [43]. e antimicrobial potential of hydrazinecarbothioamide against Bacillus subtilis, E. coli, Staphylococcus aureus, Pseudomonas aeruginosa, Paenibacillus macerans, and Salmonella typhimurium was reported by Shim et al [44].…”
Section: Well Diffusion Agar Antimicrobial Activity Of Tunichrome Was Reported By Sugumaran and Robinsonmentioning
confidence: 68%
“…According to the previous studies, some identified components such as 3-methyl-2-[4-(3-methyl-butoxy)-benzoylamino]-butyric acid [38], hexadecanoic acid [39], and phenol, 2,4-bis(1,1-dimethylethyl)- [40] exhibit high antioxidant activity. e antimicrobial activities of oxazine [41], 1,3-oxazine [42], nonanal [43], hydrazinecarbothioamide [44], triazene [45], butyric acid [46,47], (+)-trans-3,4-Dimethyl-2-phenyltetrahydro-1,4-thiazine [48][49][50], hexadecanoic acid [47], octadecanoic acid [51], spirost-8-en-11-one,3-hydroxy-, (3β, 5α, 14β.20β, 22β, 25R)- [52,53], and phenol, 2,4-bis(1,1dimethylethyl)- [40] were also well documented.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…In the lipid-signaling pathway, decarboxylation yields alkanes, methyl ketones, or 1-alkenes, and the carboxy group reduction produces 1-alkanols and aldehydes. Nonanal inhibits Penicillium cyclopium and Botrytis cinerea ’s mycelial growth by disrupting the fungal cell membrane’s integrity, leaking the cell constituents and potassium ions, enhancing the extracellular pH, the total lipid content, and the membrane permeability [ 53 , 54 ]. Moreover, the nonanal acts as an attractant for pollinators [ 55 ], is an antifeedant [ 56 ], and controls, via the activation of peripheral neurons (e.g., in Helicoverpa assulta ), the insect oviposition preference [ 57 ].…”
Section: Discussionmentioning
confidence: 99%